The learning design matrix - Mohd Kamalludeen, Rosemaliza (Centre for Teaching and Learning (CTL) and International Islamic University Malaysia (IIUM), 2018)
Instructional design models are used by instructional designers to guide the process of developing learning experiences with the aim of achieving intended learning outcomes. The Learning Design Matrix is a grid template that can be utilised by instructional designers, teachers, trainers, learning facilitators and other individuals who are interested in designing learning events that simplifies constructive alignment and addresses the needs of diverse learners all on one visual page. ADDIE, ARCS, ASSURE, and various other ID models have their own set of phases or steps, all based on sound research reflecting best learning experiences. The Learning Design Matrix aligns learning outcomes, learning activities and learning assessment on a grid while combining simplified Gagne's events of instructions to detail out activities that will be carried out in the learning event. Visual, auditory, kinaesthetic and read/write stimulus are also spelled out in the matrix to allow designers to gauge frequency of the usage of various stimulus, ensuring adequate triggers for all learning styles